Language Practices Used By People Living with Diabetes - Gonzalez, Jessica L (NSUWorks, 2021)
Individuals' experiences living with diabetes continually changes, and how they feel about their diabetes evolves throughout their lives. The purpose of this focused analysis research project was to explore how individuals who live with diabetes and who manage with an insulin pump use language practices to describe their experiences with diabetes, their self-identity, and threats to self-identity. The data set consisted of 30 interviews with 15 participants in Newfoundland and Labrador. I employed inductive content analysis to identify essential language practices, implied meaning in the conversation, intended audiences, and conversational consequences in the interviews. Understanding how people with diabetes express their experience provides insight into how individuals perceive their self-management practices and their self-identity with diabetes in different contexts. This, in turn, may aid nurses in identifying language indicators that need to be followed up in conversation to illuminate the challenges and stigma people may face in living with their diabetes.